2022
DOI: 10.3389/fimmu.2022.1035616
|View full text |Cite
|
Sign up to set email alerts
|

Tumor immune microenvironment in endometrial cancer of different molecular subtypes: evidence from a retrospective observational study

Abstract: ObjectiveTumor immune microenvironmental features may predict survival and guide treatment. This study aimed to comprehensively decipher the immunological features of different molecular subtypes of endometrial cancer.MethodsIn this retrospective study, 26 patients with primary endometrial cancer and four with recurrent disease treated in our center from December 2018 to November 2021 were included. Next-generation sequencing was performed on tumor samples. Patients were classified into four subtypes, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 53 publications
(43 reference statements)
1
15
0
Order By: Relevance
“…As we known, copy number high EC patients with the worst prognosis [48]. Previous studies have indicated that MSI type was observed relatively high percentages of CD8+T cells [49] and could benefit a lot from ICI [50,51], which was consistent with the results we have found. These findings confirm once again that EC patients in the low-risk group could be the potential ICI treatment candidates.…”
Section: Discussionsupporting
confidence: 91%
“…As we known, copy number high EC patients with the worst prognosis [48]. Previous studies have indicated that MSI type was observed relatively high percentages of CD8+T cells [49] and could benefit a lot from ICI [50,51], which was consistent with the results we have found. These findings confirm once again that EC patients in the low-risk group could be the potential ICI treatment candidates.…”
Section: Discussionsupporting
confidence: 91%
“…Cai et al [ 33 ] clustered the samples according to the infiltration of immune cells in tumor tissues and obtained three subpopulations with high, intermediate, and low immune cell infiltration, namely, C I, C II, C III, among which C I and C II patients performed adjuvant treatment better. Another study from our group [ 10 ], combining molecular subtyping with the immune microenvironment, explored the immune microenvironment characteristics of different molecular subtyping, in which the tumor mutation burden (TMB) levels of POLE mutant and MSI-H cases were significantly higher than that of the other two subtypes ( P < 0.001). He combined POLE mutant and MSI-H subtypes into the TMB high (TMB-H) subtype.…”
Section: Discussionmentioning
confidence: 99%
“… Molecular subtyping: endometrial cancer tissue and blood samples from patients were collected, sequencing was performed using a high-throughput sequencer (Illumina products, USA), and sequencing data were analyzed using a high-throughput sequencing data analysis system (Amoy Diagnostics Co., Ltd.). Based on the sequencing results, in this study, we refer to the 2013 TCGA molecular classification method [ 2 ] to classify the patients into four subtypes: POLE ultramutated, MSI-H, CNL, and CNH, and the specific subtyping was performed using Trans-PORTEC [ 9 ], as follows: (1) the mutation status of the POLE gene was detected if the pathogenic mutation of the POLE gene was judged to be POLE ultramutated; (2) a microsatellite instability (MSI) value ≥ 0.4 in a sample wild-type for the POLE gene was judged as MSI-H type; (3) TP53 mutation status was determined in microsatellite stable patients and CNH and cases without mutation were judged as CNL [ 10 ]. Immunohistochemistry: ER, PR, p53, and Ki-67 expression were detected by immunohistochemistry with an envision kit purchased from Zymed (USA).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, studying the ITME of different molecular subtypes is important. Recently studies on the ITME of different molecular types of EC have revealed that different molecular types may have different ITME (7,8). However impact of the ITME on EC remains unclear.…”
Section: Introductionmentioning
confidence: 99%